2019
DOI: 10.1371/journal.pbio.2006211
|View full text |Cite
|
Sign up to set email alerts
|

Rods contribute to the light-induced phase shift of the retinal clock in mammals

Abstract: While rods, cones, and intrinsically photosensitive melanopsin-containing ganglion cells (ipRGCs) all drive light entrainment of the master circadian pacemaker of the suprachiasmatic nucleus, recent studies have proposed that entrainment of the mouse retinal clock is exclusively mediated by a UV-sensitive photopigment, neuropsin (OPN5). Here, we report that the retinal circadian clock can be phase shifted by short duration and relatively low-irradiance monochromatic light in the visible part of the spectrum, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 83 publications
5
53
1
Order By: Relevance
“…Using a candidate gene approach similar to Buhr et al [11] they then demonstrated the absence of a lightinduced phase shift in rodless mice. They did, however, find a residual phase shift in rodless retinas when using UV light (395 nm), which they attribute to OPN5 and/or OPN1SW [12].…”
Section: Light Entrainment Of Retinal Biorhythmsmentioning
confidence: 86%
See 4 more Smart Citations
“…Using a candidate gene approach similar to Buhr et al [11] they then demonstrated the absence of a lightinduced phase shift in rodless mice. They did, however, find a residual phase shift in rodless retinas when using UV light (395 nm), which they attribute to OPN5 and/or OPN1SW [12].…”
Section: Light Entrainment Of Retinal Biorhythmsmentioning
confidence: 86%
“…Using knockout mice, they demonstrated that neither short-wavelength-sensitive cone opsins (OPN1SW), nor the orphan opsin encephalopsin (OPN3) were required, and they identified neuropsin (OPN5) as the responsible photoreceptor [11]. Contrasting these findings, Calligaro et al [12] found that rods play a crucial role in the lightinduced phase-shift of retinal biorhythms when exposed to light pulses reduced to only 15 min of duration (intensity of between 10 13 and 10 14 photons/cm 2 /s) at wavelengths up to 520 nm. Using a candidate gene approach similar to Buhr et al [11] they then demonstrated the absence of a lightinduced phase shift in rodless mice.…”
Section: Light Entrainment Of Retinal Biorhythmsmentioning
confidence: 98%
See 3 more Smart Citations